Mempelajari Pewarnaan Tahu dengan Ekstrak Pewarna Alami untuk Variasi Tampilan Tahu - Anggraini, Serly; Tamrin, Tamrin; Rahmawati, Winda; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2022)
Tofu is a food made from soybean. Tofu generally has a white or yellow color, so the addition of natural dyes from red dragon fruit peel extract, suji leaf extract, and pandan leaf extract will cause the product to have a more attractive color so that it can increase people's interest in consuming tofu.This research was conducted in April-June 2019 at the Bioprocess and Postharvest Engineering Laboratory, Department of Agricultural Engineering, Faculty of Agriculture, University of Lampung, in the Agricultural Product Technology Instrument Room, Department of Agricultural Product Technology, Faculty of Agriculture, University of Lampung, and in the residence of Mrs. Siti Jl .Arjuna Banjarrejo Village, Batanghari District, East Lampung. The research procedure was carried out by preparation of tools and ingredients, the stage of making natural coloring extracts, the calculation phase of the concentration of natural coloring extracts of 4% and 8%, and the processing stage of tofu making processing stage extracts. The treatments given were 4% and 8% concentrations in each color extract with 3 replications. The research parameters consisted of a color test using the Color Meter TES 135 A, a texture test using Brookfield Texture Analizer, and an organoleptic test of taste and aroma using 15 panelists.  The results showed that tofu with extracts of natural pandan leaves 4% concentration was the best treatment combination based on textured and organoleptic tests of taste and aroma.